Thermo-structural fatigue and lifetime analysis of a heat exchanger as a feedwater heater in power plant. (July 2020) - Hoseinzadeh, Siamak; Heyns, P. Stephan
Highlight: The real design of a shell-and-tube counter-flow heat exchanger as a feedwater heater in power plant is considered. Failure conditions are evaluated according to the ASME VIII Boiler and Pressure Vessel Code. The results of equivalent thermal stress analysis and system lifetime under two extreme loading conditions are reported. The highest equivalent thermal stresses occur at the joints of the tubes and tubes sheet and is equal to 641 and 931 MPa, respectively. The lifetimes of tubes and tube sheets are 10 5 and 10 4 cycles respectively for the valley and peak load conditions. Abstract: Today, the use of shell and tube heat exchangers has become widespread and they are used in various industries under very diverse operating conditions. Specific operating conditions make it possible to consider and simulate the operating terms and failure conditions of these converters. In this study, the design of a shell-and-tube counter-flow heat exchanger in AutoCAD software is first considered, and the system is then meshed and simulated in ANSYS 2019 software. Simulation results of temperature, pressure, heat flux and fluid velocity within the system are reported in order to understand the system performance. Failure conditions are evaluated according to the ASME VIII Boiler and Pressure Vessel Code, and the results of equivalent thermal stress analysis and system lifetime under two extreme loading conditions are reported. The highest equivalent thermal stresses under these extreme load conditions occur at the joints of the tubes and tubes sheet and is equal to 641 and 931 MPa, respectively. Also, the lifetimes of tubes and tube sheets are 10 5 and 10 4 cycles respectively for the valley and peak load conditions.